The use of social media as a tool for stakeholder engagement in health service design and quality improvement: A scoping review - Louisa Walsh; Nerida Hyett; Nicole Juniper; Chi Li; Sophie Rodier; Sophie Hill (DIGITAL HEALTH, 2021)
Background Health-related social media use is common but few health organisations have embraced its potential for engaging stakeholders in service design and quality improvement (QI). Social media may provide new ways to engage more diverse stakeholders and conduct health design and QI activities. Objective To map how social media is used by health services, providers and consumers to contribute to service design or QI activities. Methods The scoping review was undertaken using the Joanna Briggs Institute methodology. An advisory committee of stakeholders provided guidance throughout the review. Inclusion criteria were studies of any health service stakeholders, in any health setting, where social media was used as a tool for communications which influenced or advocated for changes to health service design or delivery. A descriptive numerical summary of the communication models, user populations and QI activities was created from the included studies, and the findings were further synthesised using deductive qualitative content analysis. Results 40 studies were included. User populations included organisations, clinical and non-clinical providers, young people, people with chronic illness/disability and First Nations people. Twitter was the most common platform for design and QI activities. Most activities were conducted using two-way communication models. A typology of social media use is presented, identifying nine major models of use. Conclusion This review identifies the ways in which social media is being used as a tool to engage stakeholders in health service design and QI, with different models of use appropriate for different activities, user populations and stages of the QI cycle.